Estimating the Relationship between Reading in Primary Education, Educational Attainment and Social Welfare. The Case of Extremadura (Spain) - Francisco-Javier; José Soto-Vázquez; José-Antonio Gut; Ramón Pérez-Parejo (Universidad de Navarra, 2020)
The purpose of this paper is to analyse the relationship between the Social Welfare Index and the reading habits of primary school students in Extremadura (Spain). A study has been performed which consists of two parts. First, we conducted 4,288 surveys on reading habits in 87 municipalities. Second, we calculated the social welfare index. The statistical analysis refl ects two conclusions: firstly, educational and socio-economic policies have resulted in equal opportunities that allow for similar social possibilities throughout the territory; secondly, Educational Attainment of parents is the most decisive factor in obtaining the best results in terms of students' reading habits.